AIAA SCITECH 2022 Forum 2022
DOI: 10.2514/6.2022-2330
|View full text |Cite
|
Sign up to set email alerts
|

Secondary instabilities in swept-wing boundary layers: Direct Numerical Simulations and BiGlobal stability analysis

Abstract: The evolution of secondary instabilities in a three-dimensional stationary-crossflow-dominated boundary layer is investigated by means of Direct Numerical Simulations (DNS) and linear spanwise BiGlobal stability analysis. Single-frequency unsteady disturbances and a critical stationary crossflow mode are considered. Unsteady perturbation content at 1 kHz manifests in the form of the type-III instability mechanism in the lower portion of the boundary layer in both the DNS and the stability approach. Considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
0
0
Order By: Relevance
“…For consistency with established experimental and numerical studies, the double-spectral notation (h, k) is adopted to refer to generalized CF instability modes featuring integer multiples of the reference frequency f 0 and spanwise wavenumber c 0 , namely, h ¼ f =f 0 , where f 0 ¼ 200 Hz and k ¼ c=c 0 , where c 0 ¼ 1=k 0 ; k 0 ¼ 8 mm. U HW i z , showing that the wallnormal distribution of traveling modes strongly depends on the frequency, as observed by Casacuberta et al 44 Compared with the negative traveling modes ðh; ÀkÞ, positive traveling modes ðh; þkÞ are evidently more amplified by the PA forcing. The dominance of positive traveling modes is also experimentally observed by Borodulin et al 45,46 and agrees well with previous LST predictions.…”
Section: Spanwise-wavenumber Spectrasupporting
confidence: 58%
“…For consistency with established experimental and numerical studies, the double-spectral notation (h, k) is adopted to refer to generalized CF instability modes featuring integer multiples of the reference frequency f 0 and spanwise wavenumber c 0 , namely, h ¼ f =f 0 , where f 0 ¼ 200 Hz and k ¼ c=c 0 , where c 0 ¼ 1=k 0 ; k 0 ¼ 8 mm. U HW i z , showing that the wallnormal distribution of traveling modes strongly depends on the frequency, as observed by Casacuberta et al 44 Compared with the negative traveling modes ðh; ÀkÞ, positive traveling modes ðh; þkÞ are evidently more amplified by the PA forcing. The dominance of positive traveling modes is also experimentally observed by Borodulin et al 45,46 and agrees well with previous LST predictions.…”
Section: Spanwise-wavenumber Spectrasupporting
confidence: 58%
“…The finger vortex acts as a Type-2 SI by being distributed to cover the CFV (Nakagawa et al, 2023a,b). In general, Type-1 SI and Type-2 SI can be distinguished by their generating location and frequency band (Malik et al, 1999;Högberg and Henningson, 1998;Serpieri and Kotsonis, 2016;Casacuberta et al, 2022;Chen et al, 2022), and in addition, we suggested that they are also distinguishable in terms of the turbulent energy production (Nakagawa et al, 2023a). However, in this paper, we do not make a strict distinction because they are high frequencies that play a common role in finally collapsing CFVs.…”
Section: Process Change From Path a To Path Bmentioning
confidence: 79%
“…However, few research works have paid close attention to the suction effects on the initial amplitude of dominant unstable waves in real transonic swept wings compared to experimental data. According to Saric's experimental and theoretical research [25][26][27][28][29], stationary crossflow waves, that is, when the wave frequency is equal to zero, usually dominate the crossflow instabilities in low turbulence disturbance environments. So, here, the stationary crossflow instabilities are only focused on due to their common role in aeronautical flow transitions.…”
Section: Introductionmentioning
confidence: 99%